Factores explicativos do nível de endividamento dos municípios do Norte de Portugal - Ribeiro, Nuno A. (2012)
The control of the States’ debt is, increasingly, on the agenda. Local government cannot be excluded from this effort. Thus emerges the need to create mechanisms allowing it to be managed and analysed in a credible manner. In this context, the objective of this research is to identify, for the years 2006 and 2007, the determinants of the local debt in the north of Portugal, trying to understand which ones and how they influence it. In addition to a bivariate analysis, a multiple linear regression model will be tested. The bivariate analysis findings allowed verifying that there are several factors correlated with local debt, namely debt limit, tax revenue, total expenditure, capital expenditure and current balance. The validation of the linear regression model allowed concluding that the variables debt limit, total expenditure, capital revenue and current balance are those that seem to better influence the debt level. Finally we found that the main factors which have statistically significant values in both bivariate and multivariate analysis are the same for the two years.